Adam R. GAISER, Shurāt Legends, Ibādī Identities. Martyrdom, Asceticism, and the Making of an Early Islamic Community, Columbia, South Carolina, University of South Carolina Press, 2016 - Francesca, Ersilia (Studi Magrebini, 2018)
Keywords: Recension

Il Kharigismo come concetto politico nel mondo contemporaneo. Riflessioni sullo scontro ideologico tra Al-Azhar e Sayyid Quṭb - Cascio, Roberto (Occhialì, 2018)
Keywords: Recension

Review of Ibadi Theology: Rereading Sources and Scholarly Works - Adem, Rodrigo (Journal of the American Oriental Society, 2018)
Keywords: Recension

Abdulrahman Al-Salimi and Wilferd Madelung (eds): Ibāḍī Texts from the 2nd/8th Century. (Islamic History and Civilization. Studies and Texts 133.) vi, 392 pp. Leiden: Brill. 2018. €110. ISBN 978 90 04 33064 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

سلسلة الدراسات الإباضية والعمانية المجلد الثاني: كتاب عمان وما وراء البحار - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

الإباضية في منطقة المحيط الهندي.. القسم الأول - شرق أفريقيا - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

Stuart Laing. Tippu Tip: Ivory, Slavery and Discovery in the Scramble for Africa - Kyle, Michael (Asian Affairs, 2018)
Keywords: Esclavage -- Zanzibar; Recension; Tippo Tip (1837-1905)

ARABS AND THE SCRAMBLE FOR AFRICA - The Arabs and the Scramble for Africa. By John C. Wilkinson. Sheffield, England: Equinox Publishing, 2015. Pp. xiv + 497. £70.00/$115.00, hardback (ISBN 9781781790687). - Nicolini, Beatrice (The Journal of African History, 2018)
Keywords: Recension

EISENER, R. (ed.) – Today’s Perspectives on Ibadi History - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

AL-KHARUSI, K. – Āthār al-Rabīʿ b. Ḥabīb. Edition and Study - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

AL SALIMI, A., and E. STAPLES (eds.) – The Ports of Oman - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

AL SALIMI, A., and E. STAPLES (eds.) – Oman. A Maritime History - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

Al-Kharusi Kahlan: Āthār al-Rabīʿ b. Ḥabīb. Edition and Study - Tilier, Mathieu (Bulletin critique des Annales islamologiques, 2018)
Keywords: Recension

Les Mosquees Ibadites du Djebel Nafusa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe-XIIIe siecle). By Virginie Prevost. - Sjöström, Isabella (Libyan Studies, 2018)
Keywords: Recension

Ibadi Theology: Rereading Sources and Scholarly Works. Edited by Ersilia Francesca. Studies on Ibadism and Oman, vol. 4. Hildesheim: Georg Olms, 2015. Pp. 331. €68. - Rodrigo, Adem (Journal of the American Oriental Society, 2018)
Keywords: Recension

Virginie Prevost: Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (viiie/xiiie siècle). (Society for Libyan Studies Monograph, 10.) xxi, 232 pp. London: The Society for Libyan Studies, 2016. ISBN 978 1 900971 41 6. - Aillet, Cyrille (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

Āthār al-Rabīʿ b. Ḥabīb. Edition and Study, written by Kahlan Al-Kharusi, 2016 - Rebstock, Ulrich (Die Welt des Islams, 2018)
"Āthār al-Rabīʿ b. Ḥabīb. Edition and Study, written by Kahlan Al-Kharusi, 2016 " published on 16 Mar 2018 by Brill.
Keywords: Recension

Spatial pattern of Islamic settlements of kampung Kauman Malang in the perspective of typical Mzab - Junara, Nunik; Sugeng, Triyadi S (IOP Conference Series: Earth and Environmental Science, 2018)
Keywords: Recension